A comprehensive insight into the metabolic landscape of fruit pulp, peel, and seed in two longan (Dimocarpus longan Lour.) varieties - Jing Wang; Dongliang Guo; Dongmei Han; Xuewen Pan; Jianguang Li (International Journal of Food Properties, 2020)
Longan is an ancient and popular plant with highly nutritious fruit. The pulp is the main part of the fruit which is consumed. However, the potentials of other longan fruit parts such as the peel and the seed as reservoirs of important bioactive components have not yet fully been explored. This study aimed at exploring the diversity of primary and secondary metabolites in two commercial longan varieties, i.e., Shixia and Chuliang, concerning fruit, pulp, peel, and seed based on a widely targeted metabolomics approach. A total of 706 metabolites were identified grouped into eight diverse classes of metabolites, including flavonoids, amino acids and its derivatives, alkaloids, tannins, phenolic acids, organic acids, nucleotides and derivatives, lipids, and lignans. Chuliang peel showed a higher accumulation of metabolites viz. flavonoids, alkaloids, and tannins, while Shixia seeds showed abundance in amino acids, organic acid, nucleic acids and its derivatives. Chuliang pulp showed relatively higher accumulation of lipids when compared with other fruit parts. Differential metabolome profiling between fruit parts indicates the prevalence of key metabolites, i.e., O-Phosphocholine, betaine, piperidine, L-Arginine, and L-Phenylalanine, in seed and peel of the longan fruit. The findings in this research provide a new glance on the nutritional value and biochemical basis of longan fruit pharmaceutical value, with emphasis on valorization of longan peel and seed tissues for their pharmaceutical properties and nutritional values.